Maternal stress coping as related to children‘s emotional and behavioral problems - Jusienė, Roma; Platkevičiūtė, Vaida (Psichologija, 2003)
Coping is defined as the cognitive and behavioral efforts used to manage specific external and internal demands, appraised as taxing or exceeding a person?s resources. Some of coping strategies are considered to be adaptive, while others - maladaptive. Excessive use of maladaptive stress coping strategies is found to correlate with emotional or behavior problems. There are only few attempts to study coping in parenting situation, indicating that the stress and coping model is useful in exploring the complex process of adaptation to parenting, and relating it to the psychological adjustment of the children. On the one hand, children learn stress coping strategies from their parents. On the other hand, the parental mood as mediated by their coping is considered to be the important factor influencing children's psychological adjustment.The present study aims to evaluate the relationship between maternal coping and emotional and behavioral problems of children in intact and divorced families. Mothers of 183 children (age 2 to 10 years) answered two questionnaires: Stress Coping Strategies questionnaire (Elklit, 1996) and Child Behavior Checklist (Achenbach, 1991).The results show the strong positive correlation between maladaptive maternal coping and the psychological adjustment of children. Maternal coping as well as children's emotional and behavior problems are related to mothers' education. Mothers with a lower education degree use more maladaptive coping strategies, particularly avoiding coping. They denote more children's behavioral and emotional problem too. Our results show that psychological adjustment of children who live without father isn't worse, then psychological adjustment of children who live with both parents. The results reveal that single mothers use more adaptive coping, then those, who live in intact families. The results of regression analysis show that emotional coping used by mother and her lower education level predict higher rates of children's emotional and behavioral problems.Mothers were the only informant about children's psychological adjustment in this study. Further steps related to this topic could be analyzing whether the relation between maternal stress coping and children's emotional and behavioral problems remains when the latter are indicated by other informants.
Keywords: maternal; stress coping; children; emotional problems; behavioral problems